Malocclusion in deciduous dentition of Saudi children: A cross-sectional study (Bangladesh Journal of Medical Science, 2012)
Background: Occlusal characteristics of the primary dentition vary among populations and ethnic groups. Materials and Methods: This cross-sectional study aimed to record various primary dentition parameters in 700 Saudi children, 2-6 year-old, was divided into 4 age groups and was randomly selected to observe the differences between the age groups. Results: 55.6% of the children had a 'flush terminal plane' molar relationship. The proportion of children with distalstep molar relationship was significantly lower 23 (3.2%). The degree of overbite was significantly less in the 5-year-olds than in the 3-year-olds. The majority of the children (80.7%) had spaced dentition. The prevalence of anterior cross bite was 0.7% and of open bite was 0.3%. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12608 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12